Structure of Titan's induced magnetosphere under varying background magnetic field conditions: Survey of Cassini magnetometer data from flybys TA–T85. Issue 4 (22nd April 2013) - Simon, Sven; van Treeck, Shari C.; Wennmacher, Alexandre; Saur, Joachim; Neubauer, Fritz M.; Bertucci, Cesar L.; Dougherty, Michele K.
Abstract : [1] Cassini magnetic field observations between 2004 and 2012 suggest the ambient field conditions near Titan's orbit to differ significantly from the frequently applied pre‐Cassini picture (background magnetic field homogeneous and perpendicular to Titan's orbital plane, stationary upstream conditions). In this study, we analyze the impact of these varying background field conditions on the structure of Titan's induced magnetosphere by conducting a systematic survey of Cassini magnetic field observations in the interaction region during flybys TA–T85 (July 2004–July 2012). We introduce a set of criteria that allow to identify deviations in the structure of Titan's induced magnetosphere—as seen by the Cassini magnetometer (MAG)—from the picture of steady‐state field line draping. These disruptions are classified as "weak", "moderate", or "strong". After applying this classification scheme to all available Titan encounters, we survey the data for a possible correlation between the disruptions of the draping pattern and the ambient magnetospheric field conditions, as characterized by Simon et al . [2010a]. Our major findings are: (1) When Cassini is embedded in the northern or southern lobe of Saturn's magnetodisk within a ± 3 h interval around closest approach, Titan's induced magnetosphere shows little or no deviations at all from the steady‐state draping picture. (2) Even when Titan is embedded in perturbed current sheet fields during an encounter, the notion of draping the average background field around the moon's ionosphere is still applicable to explain MAG observations from numerous Titan flybys. (3) Only when Titan is exposed to intense north‐south oscillations of Saturn's current sheet at the time of an encounter, the signatures of the moon's induced magnetosphere may be completely obscured by the ambient field perturbations. (4) So far, T70 is the only flyby that fully meets the idealized pre‐Cassini picture of the Titan interaction (steady background field perpendicular to Titan's orbital plane, steady upstream flow, unperturbed induced magnetosphere). Key Points: Only weak influence of ambient perturbations on Titan's induced magnetosphere New classification scheme for Cassini MAG data from flybys TA–T85 Only T70 fully meets the idealized pre‐Cassini picture of the Titan interaction